Tempo e espaço no processo de iniciação científica na Educação Básica - Corrêa, André Roberto de Arruda (2024)
In recent decades, an immense number of transformations have occurred in society, whether religious, cultural, social, political, and/or economic. These changes have directly interfered in the field of education, as the two institutions closely linked to education – the family and the school – no longer play the same role as before. Thus, in the contemporary world, the educational role of the family has become secondary, as parents' numerous concerns with work, sociocultural growth, and the acquisition of material goods are often placed in the foreground. This means, in practice, that family education has been transferred to the school. However, those passive students, who awaited their teachers' lectures, no longer exist. The characteristics of today's students reflect individuals connected to new technologies and social media. This new reality, this new student body, has rendered that model of school considered successful in the 19th century obsolete. Consequently, it becomes necessary to rethink the teaching-learning process and classroom practices to meet the demands of students in this century, as the relationship between teacher and student ceases to be vertical and culturally imposed and becomes one of partnership and shared responsibility in the construction of knowledge. In this context, understanding the classroom as a space-time for both the teacher and the student creates an environment of sharing, where they can together engage in learning activities. Examples of this include debates, case studies, research, question presentations, clarification of doubts, and problem-solving through Scientific Initiation. Today, education certainly exists in a context of deconstruction and reconstruction of the teacher's role; it is a time that calls for reflection on the continuous need to learn and relearn how to be a teacher. Thus, given the above, the initial problem of this work consists of answering: How are the learning process and learning through investigation being developed in basic education? In this sense, the objective of this work is to analyze the conception of the learning process, the interactions between teachers and students, and learning through investigation, in light of the BNCC and the Report of the International Commission on the Futures of Education – Unesco (2022). Based on bibliographic research and qualitative field research, this study aimed to identify and analyze the didactic-pedagogical possibilities of Scientific Initiation activities, which, through experience in basic education, have proven to be an effective pedagogical practice for a meaningful learning process for students. Thus, it highlights the connection between Scientific Initiation and the teaching-learning process in student education, leading to the hypothesis that the didactic-pedagogical strategy of Scientific Initiation qualitatively transforms this process, making it meaningful. Bibliographic sources dealing with the construction of knowledge in basic education were consulted. As a result, epistemic support for understanding and pedagogical practice that enables effective student learning is highlighted